The Effect of Giving Shallot Extract (Allium Cepa L) and NPK Fertilizer on the Growth of Green Mustard Plants (Brassica Juncea L) - Irnawati, Diah Harun; Kusmiyati, Kusmiyati; Raksun, Ahmad (Jurnal Pijar Mipa, 2025)
Plant growth and development require nutrients, which can be given through fertilization in the form of organic or inorganic fertilizers. This study aims to determine the effect of providing shallot extract, NPK fertilizer, and a combination of both on the growth of mustard greens. This study used a two-factorial, Completely Randomized Design (CRD) consisting of NPK fertilizer and shallot extract treatments, each using five levels with three replications. The parameters observed were plant height, number of leaves, leaf area, plant fresh weight, and plant dry weight. The data obtained were analyzed using two-way ANOVA and continued with the Duncan multiple range test. The results of the ANOVA test showed that the main factor of NPK fertilizer obtained a value of (sig) ˂ 0.05, the main factor of organic fertilizer was red onion extract, and the interaction factor obtained a value of (sig) ˃ 0.05. The study results showed that the administration of NPK fertilizer can increase plant height, number of leaves, leaf area, wet weight, and dry weight of green mustard plants. The administration of shallot extract can increase plant height and the number of green mustard leaves. Still, it cannot increase green mustard plants' leaf area and wet and dry weight. The administration of a combination of NPK fertilizer and shallot extract cannot increase plant height, number of leaves, leaf area, wet weight, and dry weight of green mustard.